2015
DOI: 10.11607/ofph.1221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Human Intraoral Thermal Sensitivity with Simple Devices in the Clinic: Implications for Orofacial Pain Conditions

Abstract: The reliability of intraoral thermal sensitivity recorded with the 5-mm-diameter device varied greatly between different sites. Nonetheless, with this caveat in mind, the study did document that semiquantitative assessment of intraoral thermal sensitivity is feasible and applicable for clinical studies in different intraoral pain conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…With regards to the within‐device difference between temperatures, the NRS scores to 50 °C stimulation were significantly higher than all other tested temperatures and NRS scores to 5 °C stimulation were higher than to 20 and 40 °C. These findings are in agreement with the findings in the study of Naganawa et al., () in which it was found that the NRS scores for stimulation at room temperature were significantly lower than stimulation with 5 and 51 °C as could be expected.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…With regards to the within‐device difference between temperatures, the NRS scores to 50 °C stimulation were significantly higher than all other tested temperatures and NRS scores to 5 °C stimulation were higher than to 20 and 40 °C. These findings are in agreement with the findings in the study of Naganawa et al., () in which it was found that the NRS scores for stimulation at room temperature were significantly lower than stimulation with 5 and 51 °C as could be expected.…”
Section: Discussionsupporting
confidence: 93%
“…In total, nine aluminium devices were produced, with the same tip configuration at both ends of the device, so that both of the ends could be used for the testing (Fig. ) (Naganawa et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations